Numerical Method for the Time Fractional Fokker-Planck Equation (Advances in Applied Mathematics and Mechanics, 2021)
In this paper, a new numerical algorithmfor solving the time fractional Fokker-Planck equation is proposed. Theanalysis of local truncation error and the stability of this method areinvestigated. Theoretical analysis and numerical experiments show thatthe proposed method has higher order of accuracy for solving thetime fractional Fokker-Planck equation.